Combining Evolutionary Inference and Metabolomics to Identify Plants With Medicinal Potential - Mawalagedera, Sundara M. U. P.; Callahan, Damien L.; Gaskett, Anne C.; Rønsted, Nina; Symonds, Matthew R. E. (Frontiers in Ecology and Evolution, 2019)
Plants have been a source of medicines in human cultures for millennia. The past decade has seen a decline in plant-derived medicines due to the time-consuming nature of screening for biological activity and a narrow focus on individual candidate plant taxa. A phylogenetically informed approach can be both more comprehensive in taxonomic scope and more systematic, because it allows identification of evolutionary lineages with higher incidence of medicinal activity. For these reasons, phylogenetics is being increasingly applied to the identification of novel botanic sources of medicinal compounds. These biologically active compounds are normally derived from plant secondary or specialized metabolites generally produced as induced responses and often playing a crucial role in plant defence against herbivores and pathogens. Since these compounds are typically bioactive they serendipitously offer potential therapeutic properties for humans, resulting in their use by traditional societies and ultimately drug lead development by natural product chemists and pharmacologists. The expression of these metabolites is likely the result of coevolutionary processes between plants and the other species with which they interact and effective metabolites are thus selected upon through evolution. Recent research on plant phylogeny coupled with metabolomics; which is the comprehensive analysis of metabolite profiles, has identified that related taxa produce similar secondary metabolites, although correlations are dependent also on environmental factors. Modern mass spectrometry and bioinformatic chemical networking tools can now assist high throughput screening to discover structurally related and potentially new bioactive compounds. The combination of these metabolomic approaches with phylogenetic comparative analysis of the expression of metabolites across plant taxa could therefore greatly increase our capacity to identify taxa for medicinal potential. This review examines the current status of identification of new plant sources of medicine and the current limitations of identifying plants as drug candidates. It investigates how ethnobotanic knowledge, phylogenetics and novel approaches in metabolomics can be partnered to help in characterizing taxa with medicinal potential.